How do information specialists keep up to date? - TAY, Aaron (Institutional Knowledge at Singapore Management University, 2022)
The working environment of information specialists is undergoing profound changes. This is primarily due to rapid advances in digitalization and automation. New databases are being set up or new functions added to established databases. At the same time, data processing and analysis have reached a new level (e.g. through machine learning). In addition, many new software tools to support daily work are being developed. But how do information specialists find out about new developments and assess the practical suitability of new tools? Nowadays, an abundance of information on new developments in information retrieval can be found on the Internet. In an online session hosted by Elke Hausner from the Institute for Quality and Efficiency in Health Care, Helen King from Sage Publishing Ltd, Hannah O’Keefe from Newcastle University and Aaron Tay from Singapore Management University will present their Internet activities (including newsletters, blogs, and Twitter) and talk about their work and future developments. Musings about librarianship (http://musingsaboutlibrarianship.blogspot.com): A blog by Aaron Tay, who regularly reports on new (technical) developments in librarianship.